2005
DOI: 10.1124/mol.104.009092
|View full text |Cite
|
Sign up to set email alerts
|

Akt Is Essential for Insulin Modulation of Amphetamine-Induced Human Dopamine Transporter Cell-Surface Redistribution

Abstract: Uptake by the dopamine transporter (DAT) is the primary pathway for the clearance of extracellular dopamine (DA) and consequently for regulating the magnitude and duration of dopaminergic signaling. Amphetamine (AMPH) has been shown to decrease simultaneously DAT cell-surface expression and Dopaminergic neurotransmission is determined by extracellular DA levels, which in turn are regulated principally by DAT-mediated DA reuptake. Because DA uptake capacity depends on the turnover rate of an individual transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
165
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(179 citation statements)
references
References 46 publications
12
165
0
1
Order By: Relevance
“…The possible direct effects [11][12][13] of insulin on the mesoaccumbens DA neurons are dependent on this principle. In particular, it has been reported that insulin increases DA uptake in striatal tissue from >24 h fasted rats [12] and following amphetamine incubation in rat striatal synaptosomes and HEK transfected with hDAT preincubated with insulin [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible direct effects [11][12][13] of insulin on the mesoaccumbens DA neurons are dependent on this principle. In particular, it has been reported that insulin increases DA uptake in striatal tissue from >24 h fasted rats [12] and following amphetamine incubation in rat striatal synaptosomes and HEK transfected with hDAT preincubated with insulin [11].…”
Section: Discussionmentioning
confidence: 99%
“…Central administration of insulin also has been shown to increase DA transporter (DAT) mRNA in the VTA/SNpc [10]. This increase in transporter likely influences DA signaling, since exogenously administered insulin has been shown in vitro to increase DA uptake in striatal tissue [11,12] and human DATtransfected cells [11,13]. On this basis, the present experiments focused on the role of acute elevation in plasma insulin on mesoaccumbens DA function.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that ICV insulin increases DAT mRNA (42), and that in vitro insulin reverses the effect of acute, in vivo, food restriction to decrease DA re-uptake (i.e., insulin stimulates DAT function) (10). Subsequent studies in cellular systems have demonstrated that this action of insulin is caused by enhanced recruitment of DATs to the cell membrane and is dependent on insulin-stimulation of the PI3 kinase pathway (43). This collective set of evidence strongly suggests that the DAT is likely a physiological target of insulin action.…”
Section: Cns Sites Of Action For Adiposity Signal Modulation Of Food mentioning
confidence: 99%
“…Dopamine uptake was decreased in synaptosomes from rats made hypoinsulinemic by food deprivation and was restored by administration of insulin . These effects appear to be the result of insulin acting on receptors (insulin, IGF-1) since inhibition of insulin signaling caused dopamine transporters to be translocated away from the plasma membrane, thereby reducing dopamine transport (Carvelli et al, 2002;Garcia et al, 2005). In addition to effects on dopamine uptake, insulin can also modulate other components of the dopamine system; for example, hypoinsulinemic rats show decreased synthesis (Saller, 1984) and turnover (Kwok and Juorio, 1986;Lim et al, 1994) of dopamine and they are hyporesponsive to the behavioral effects of direct-acting dopamine drugs (Sevak et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%